Study Of The Redox And Acid-Base Properties Of Soda-Lime Silicate Glass: Application To The High Temperature Corrosion Of Nickel-Based Alloys And Ceramic Materials - Abdullah, Tuti Katrina (2014)
The corrosion behaviour of chromia (Cr2O3) and alumina (Al2O3) forming alloys in soda-lime silicate melts was studied by using 'raw immersion' technique which was coupled with electrochemical measurements. The combination of both techniques leads to the determination of the general aspects of the corrosion by the molten glass as well as the redox reactions and the kinetics that rule the corrosion process. The results revealed that Al2O3 is not able to provide protection against corrosion by molten glass since it has a high dissolution in the melt. However Cr2O3 forming alloy could resist against corrosion by molten glass if the alloy was subjected to a preoxidation treatment in air before the immersion. As the durability of the Cr2O3 layer is linked to the competition between the oxide growth and its dissolution in the melt, the physicochemical properties of Cr2O3 in molten glasses were then thoroughly studied in order to understand the influence of different parameters on the limit of Cr2O3 solubility. The works were conducted by taking into account the influence of temperatures (T), oxygen fugacities (fO2) and the glass compositions on the solubility of Cr2O3 in the melts. The preliminary kinetics study revealed that the time to reach equilibrium varies with the parameters (T, fO2 and glass compositions). However, a compromising equilibrium time was chosen in order to satisfy all the problems encountered.